A brief measure for school-related achievement emotions: The achievement Emotions Adjective List (AEAL) for secondary students. Issue 3 (4th May 2022) - Raccanello, Daniela; Brondino, Margherita; Crescentini, Alberto; Castelli, Luciana; Calvo, Spartaco
ABSTRACT: The Achievement Emotions Adjective List (AEAL) is a brief self-report multi-item questionnaire deputed to assess ten achievement emotions, namely enjoyment, pride, hope, relief, relaxation, anxiety, anger, shame, hopelessness, and boredom. This study aimed at describing the initial construction and validation of the AEAL focusing on school-related emotions. We involved 2874 Swiss 10 th to 13 th graders ( Mage   = 16.87, SD  = 1.41, 56% females), who completed the 30-item version of the AEAL, a measure of value, and the School Attitude Assessment Survey-Revised. Findings supported the reliability of the instrument. As for construct validity, a ten-factor model best fit the data; also, partial scalar measurement invariance across grade level and gender was confirmed. As for predictive validity, achievement emotions related significantly to control-value appraisals, achievement goals, attitudes towards teachers/classes, attitudes towards school, and motivation/self-regulation, with some exceptions. Findings provide evidence on the goodness of the AEAL to assess secondary students' achievement emotions as a brief, simple, and not-invasive instrument. Implications for research are discussed.